2013
DOI: 10.1103/physrevlett.110.107005
|View full text |Cite
|
Sign up to set email alerts
|

Low-Field Superconducting Phase of(TMTSF)2ClO4

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…ρ s (T ) can be well described within the single-gap BCS s-wave scenario with (0) = 1.07(4) meV. The magnetic penetration depth was estimated to λ(0) = 785(20) nm, which is significantly large but consistent with the λ(0) values of other low-dimensional superconductors [38][39][40][41][42][43]. For layered superconductors, such as cuprates [44] and iron chalcogenides [45], it has been observed in the past that the penetration depth increases with increasing layer separation, i.e., when the superfluid density goes from 3D to 2D nature.…”
supporting
confidence: 65%
“…ρ s (T ) can be well described within the single-gap BCS s-wave scenario with (0) = 1.07(4) meV. The magnetic penetration depth was estimated to λ(0) = 785(20) nm, which is significantly large but consistent with the λ(0) values of other low-dimensional superconductors [38][39][40][41][42][43]. For layered superconductors, such as cuprates [44] and iron chalcogenides [45], it has been observed in the past that the penetration depth increases with increasing layer separation, i.e., when the superfluid density goes from 3D to 2D nature.…”
supporting
confidence: 65%
“…The engineering of conducting states at the interface of oxide [2] and organic materials [3] has demonstrated the ability to produce new types of 2-dimensional (2D) conducting systems with novel properties. Parallel to this, systems that host naturally occurring lower-dimensional electron systems supported by a highly anisotropic structures have also shown promise for realizing such states, including p-wave superconductivity [4] and spin liquid [5]. Particularly regarding these naturally anisotropic materials, the vital question remains of to what extent such low-dimensional electronic systems are accessible to measurement and utilization and how those dimensional changes modify electronic structure.…”
mentioning
confidence: 98%
“…Since the combination of spin interchange, parity, and relative time reversal has to be odd for a pair of electrons, the found odd-frequency gap symmetries are either both even under spin and even under parity or odd under spin and odd under parity.Consequently, for an experimental identification of the symmetry of a bulk superconducting gap in simple single-band systems, it is required to measure at least two of the three above mentioned information, e.g., as performed in Ref. [34]. Even though signals for the experimental verification of odd-frequency states are often discussed in connection to systems which explicitly break time-reversal symmetry [31][32][33], our paper reveals that odd-frequency solutions do not require a time-reversal breaking potential.…”
Section: Resultsmentioning
confidence: 99%
“…Also, odd-frequency states were discussed in connection to time-reversal topological superconductivity in double Rashba wires, where it was found that odd-frequency pairing is strongly enhanced in the topological state [30]. For some of the above mentioned systems, the respective signatures of odd-frequency correlations could also be verified experimentally [31][32][33][34]. An extensive discussion of edge-states and topology in superconductors including odd-frequency gap functions was communicated by Tanaka, Sato and Nagaosa [35].…”
mentioning
confidence: 99%